2020
DOI: 10.1016/j.jcte.2020.100243
|View full text |Cite
|
Sign up to set email alerts
|

Dried urine and salivary profiling for complete assessment of cortisol and cortisol metabolites

Abstract: Highlights Dried urine is an alternative to liquid urine for measuring cortisol and its metabolites. 4-spot urine sampling is representative of a 24-hour urine collection. 4-spot urinary cortisol measures reflect the diurnal pattern of change in cortisol. Comprehensive profiling of cortisol is viable using both saliva plus dried urine samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…Still, agreement between 24-h urine collections and early-morning, single spot urine collections for hormonal analysis are often poor [ 28 ]. This study now extends our prior findings [ 11 , 14 ] to show that the increase to four spot urines spaced throughout the waking hours provides better coverage of the hormonal output for all the male and female reproductive hormones and metabolites, resulting in strong agreement with 24-h urine measures.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Still, agreement between 24-h urine collections and early-morning, single spot urine collections for hormonal analysis are often poor [ 28 ]. This study now extends our prior findings [ 11 , 14 ] to show that the increase to four spot urines spaced throughout the waking hours provides better coverage of the hormonal output for all the male and female reproductive hormones and metabolites, resulting in strong agreement with 24-h urine measures.…”
Section: Discussionsupporting
confidence: 83%
“…In fact, repeated assessments over a month demonstrated that the dried urine collections could accurately recreate the changes observed in serum during the menstrual cycle [ 11 ]. In addition, not only does the 4-spot urine method accurately represent a 24-h urine collection for urinary cortisol, cortisone, and cortisol metabolites, but it can also be used to represent the expected diurnal pattern observed with salivary measures, if each of the four collections is considered individually [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations